Motorcycle helmet: Part II. Materials and design issues - Shuaeib, F.M; Hamouda, A.M.S.; Hamdan, M.M; Radin Sohadi, Radin Umar; Hashmi, M.S.J. (Elsevier, 2002)
The main objective of this paper is to formulate a methodology, which could be used for material selection and basic design of motorcycle helmets. The importance of simplified solutions to motorcycle helmet material selection and design are first highlighted. Two methods are presented. The first approach is based on energy absorption theory for packaging design and also was used for bicycle helmets design with some adjustments. This method is reviewed and modified to cope with the motorcycle helmet design requirements. The second approach is also based on energy absorption principle. This method was developed for packaging design but the same principles could be employed to the motorcycle helmet problem. It was found that the two approaches have the same energy absorption principles but differ in the way of formulation and utilization. These differences could have significant effect on the results particularly the energy per unit volume calculation. However, both procedures could be used as a useful tool for the helmet foam material selection and helmet preliminary analysis and design. Using these energy approaches together with advanced computational techniques could reduce the lead-time of helmet design and manufacture.